2021
DOI: 10.12911/22998993/132605
|View full text |Cite
|
Sign up to set email alerts
|

Comparison the Adsorption Capacity of Ukrainian Tuff and Basalt with Zeolite–Manganese Removal from Water Solution

Abstract: Manganese is an undesirable element in tap water but is common in the groundwater. Several methods can be used for manganese removal, including adsorption. Mined rocks are commonly evaluated as adsorbents and it was the objective of this paper-to investigate the Ukrainian volcanic tuff and basaltic rock from the Ivanodolinsky quarry and compare it with Ukrainian zeolite as well as with literature data. The research was based on equilibrated batch tests at a temperature of 10°C and slightly acidic pH. The data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Iron-rich natural materials such as volcanic tuff, some kaolins, zeolites, and others that contain hematite (Fe 2 O 3 ) have shown a higher adsorption capacity for heavy metals compared to those materials that do not contain them or contain them in very low concentrations. So, for example, the sorption capacity of Mn 2+ by iron-containing tuff is more than 8.5 mg/g, and by basalt, it is 4.3 mg/g [12,13]. In addition, in the research study that compared the Ni 2+ sorption capacity of different kaolins, it was found that with hematite content in kaolin over 3.5%, the sorption capacity was approximately 2.5 times higher [14].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Iron-rich natural materials such as volcanic tuff, some kaolins, zeolites, and others that contain hematite (Fe 2 O 3 ) have shown a higher adsorption capacity for heavy metals compared to those materials that do not contain them or contain them in very low concentrations. So, for example, the sorption capacity of Mn 2+ by iron-containing tuff is more than 8.5 mg/g, and by basalt, it is 4.3 mg/g [12,13]. In addition, in the research study that compared the Ni 2+ sorption capacity of different kaolins, it was found that with hematite content in kaolin over 3.5%, the sorption capacity was approximately 2.5 times higher [14].…”
Section: Introductionmentioning
confidence: 94%
“…Experimental parameters for pulse generation were set by the UTP3305C power supply unit via the RS-232 interface (Figure 1). due to the short time required to reach adsorption equilibrium and the high values of the maximum sorption capacity [12]. So, it is important to continue these studies on creating the conditions that would allow one to obtain iron-containing magnetic materials of the required phase composition and particle sizes during the processing of industrial waste-exhausted etching solutions with minimal energy consumption.…”
Section: Experimental Setmentioning
confidence: 99%
See 1 more Smart Citation
“…Plante et al [17] demonstrated that plagioclase controlled Ni mobility through sorption in waste rock piles of the Tio mine. More recently, Reczek et al [104] and Trach et al [105] stated that volcanic tuff and basalt effectively adsorb Mn. Therefore, the next step of the geochemical assessment of Akasaba West materials should involve sorption experiments to investigate the effect of the sorption capacity of plagioclase on water quality.…”
Section: Model Benchmarking (I) D1 Weathering Cellmentioning
confidence: 99%
“…The adsorption occurs quickly in a slightly acidic environment and at a low temperature of 10 • C, the typical conditions for groundwater treatment. Additionally, the adsorption capacity of Ukrainian tuff from the Ivanodolynsky quarry (Rivne region) is twice that of basalt and zeolite [44,45].…”
Section: Introductionmentioning
confidence: 99%